The impact of Mayer–Rokitansky–Küster–Hauser Syndrome on Psychology, Quality of Life, and Sexual Life of Patients: A Systematic Review - Ermioni Tsarna; Anna Eleftheriades; Makarios Eleftheriades; Emmanouil Kalampokas; Maria-Konstantina Liakopoulou; Panagiotis Christopoulos (Children, 2022)
Background: Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome is a rare congenital syndrome characterized by uterovaginal agenesis. Most patients are diagnosed during adolescence, when body image and sexual identity are shaped. Our main objective was to investigate how MRKH syndrome affects psychology, quality of life (QoL), and the sexual life of patients compared with non-affected individuals. Methods: Original peer-reviewed research papers examining psychological outcomes, QoL, and sexual function of MRKH patients were searched in PubMed. Titles, abstracts, and full text from potentially eligible records were reviewed by two independent reviewers. Case reports and papers published not in English were excluded. Results: Our search identified 63 records, of which 20 were included: 10 examined psychological and psychosocial outcomes, 14 examined sexual function outcomes, and 6 examined QoL outcomes. Results may be affected by selection bias and confounding due to differences between MRKH patients and controls. Conclusions: MRKH could be associated with a higher prevalence of anxiety and depression symptoms and social insecurity compared with women of a similar age without the condition. MRKH could also be associated with greater pain and discomfort during sexual intercourse and limitations in arousal, lubrication, and orgasm. MRKH patients more commonly experience impairment of mental-health-related QoL, but physical-health-related QoL is not affected.